Analysis of the variations in dry matter yield and resource use efficiency of maize under different rates of nitrogen, phosphorous and water supply. (27th May 2020) - Momen, Ali; Koocheki, Alireza; Mahallati, Mehdi Nassiri
Abstract: Increasing resources use efficiency in intensive cultivation systems of maize ( Zea mays L.) can play an important role in increasing the production and sustainability of agricultural systems. The objectives of the present study were to evaluate DM yield and the efficiency of inputs uses under different levels of water, nitrogen (N) and phosphorus (P) in maize. Therefore, three levels of irrigation including 80 (ETc80 ), 100 (ETc100 ) and 120% (ETc120 ) of crop evapotranspiration were considered as the main plots, and the factorial combination of three levels of zero (N0 ), 200 (N200 ) and 400 (N400 ) kg N ha −1 with three levels of zero (P0 ), 100(P100 ) and 200 (P200 ) kg P ha −1 was considered as the sub plots. The results showed that increasing the consumption of water and P was led to the reduction of N and P utilization efficiency, while RUE increased. WUE was also increased in response to application of N and P, but decreased when ETC increased. DM yield under ETc80 treatment reduced by 11 and 12%, respectively, compared to ETc100 and ETc120 which was due to reduction of cumulative absorbed radiation ( R abs (cum)) and RUE. Under these conditions, changes of stomatal conductance (gs) had little effect on DM yield. It was also found that N limitation caused 11 and 20% reduction in DM yield compared to N200 and N400, respectively. This yield reduction was mainly the result of decrease in RUE. By decreasing Rabs (cum), P deficiency also reduced DM yield by 5 and 9%, respectively, relative to P100 and P200 treatments.